The narrative technique of The life of Charlotte Brontë : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Morris, Raewyn Delia (Massey University, 1987)
The following discussion of The Life of Charlotte Bronte is an examination of the narrative techniques Elizabeth Gaskell employs in the biography. The structure of The Life of Charlotte Bronte is such that the narrative 'voice' of Elizabeth Gaskell is heard in alternation with the 'voice' of Charlotte Bronte, the latter through the numerous letters which Gaskell has selected and placed throughout the biography. Chapter One of the discussion indicates the ways in which Gaskell has divided the text into volumes and chapters. Gaskell's methods in organising the overall structure of the biography are important because they highlight issues that recur when studying Gaskell's other narrative techniques. Chapter Two examines the chronological sequence to show in particular the effect on the text of the large number of chronological disruptions. These disruptions play a major role in providing background material concerning Charlotte. Chapter Three considers several important features of the narrative including digression, anecdote, summarisation of incidents, dramatisation of scenes, method in introducing and describing characters, and, finally, use of dialogue. Chapter Four looks at the issue of judgement in the biography. The narrator states in the text that it is not her role to judge, yet she does so often. As well as considering this point, I have examined the ways in which she passes judgement. Finally, Chapter Five considers Gaskell's characterisation of Charlotte as a tragic heroine. The focus in this chapter is on Gaskell's use of affective language; the selective manner in which she includes Charlotte's letters in the text is also taken up for discussion.
Keywords: Gaskell, Elizabeth Cleghorn 1810-1865; Technique